2015
DOI: 10.1186/s13019-015-0328-4
|View full text |Cite
|
Sign up to set email alerts
|

Right versus left transthoracic approach for lymph node-negative esophageal squamous cell carcinoma

Abstract: BackgroundTo compare the right and left transthoracic approach on the post-operative survival of patients with lymph node-negative esophageal squamous cell carcinoma.MethodsSix hundred and ninety-five ESCC patients who underwent esophagectomy between 1990 and 2005 were retrospectively enrolled in the present study and were confirmed by histology to be of no lymph node metastasis. Those who had received neoadjuvant chemotherapy or radiotherapy were excluded from the study. Patients were divided into two groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…In contrast, in China, the most commonly used surgical approaches for the resection of EC include the McKeown and Sweet approaches . Recently, the Ivor Lewis and MIE approaches have been increasingly adopted in China . Different surgical approaches between China and other countries may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in China, the most commonly used surgical approaches for the resection of EC include the McKeown and Sweet approaches . Recently, the Ivor Lewis and MIE approaches have been increasingly adopted in China . Different surgical approaches between China and other countries may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…However, for EC patients with negative upper mediastinal LNs who are in need of esophagectomy, there is debate over the optimal approach. For example, a recent study comparing right and left transthoracic approaches on the survival of patients with LN negative esophageal squamous cell carcinoma demonstrated that the left transthoracic approach is superior to the right in terms of surgical and oncological outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Ist der Magen nicht als Conduit verfügbar, kann alternativ Kolon verwendet werden [2]. Für das Standardverfahren ist ein linksthorakaler Zugang möglich, jedoch wird aufgrund der deutlich besseren Exposition der thorakalen Lymphknoten in der Regel ein höherer rechtsthorakaler Zugang gewählt (Ivor-Lewis-Operation, [46]). Wegen der recht hohen Komplikationsrate an der Ösophagusanastomose (historisch bis zu 25 %) und der oft schwierigen Therapieoptionen bei intrathorakaler Leckage wurde lange Zeit die fast komplette Entfernung des Ösophagus mit Anlage einer zervikalen Anastomose (McKeowan-Operation) favorisiert, auch wenn dies onkologisch nicht erforderlich war.…”
Section: Ausmaß Der Resektion Und Rekonstruktionunclassified
“…Ma et al demonstrated that operation approach (left or right approach) was not risk factor for long term survival by Cox regression analysis in patients after esophagectomy, although univariable analysis showed that operation approach was an unfavorable prognostic factor for long term survival. While other factors such as tumor staging and age were unfavorable prognostic factors for long term survival in patients after esophagectomy (10). Recently, Li et al conducted a randomized controlled study comparing the difference in postoperative complications between Sweet and Ivor approached and concluded that both approaches are safe procedures with low mortalities.…”
Section: Cost Of Sweet Approach Was Lower Than That In Open Ivormentioning
confidence: 99%
“…Fu et al reported that it is easier to perform systemic lymphadenectomy via right thoracic approach than left approach and the local recurrence is reduced and long-term survival improved (9). On the contrary, Ma J and Ma Q reported that Sweet approach was associated with reduced duration of operation, decreased complication rate, similar long term survival in esophageal cancer patients (7,10). A meta-analysis including 15 studies demonstrated that two approaches had similar long term effect (8).…”
Section: Introductionmentioning
confidence: 99%